Corporate Strategy for Emerging Defense Industry: The Case of PT Pindad’s Market Entry into The Middle East - Petherus, Valentino; Kristiyono, Hasto (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
This research aims to formulate an effective corporate strategy for PT Pindad to penetrate the Middle East defense market. Using the AFI (Analyze–Formulate–Implement) framework as a foundation, the study applies PESTEL, Porter’s five forces, VRIO, and SWOT analyses to comprehensively evaluate the current conditions. Data collection was conducted through in-depth interviews with key stakeholders. Findings indicate that the Middle East presents an extremely potential market but with a highly competitive landscape. Based on the Ansoff matrix, this research proposes a stage-based corporate strategy, beginning with market development, leveraging PT Pindad’s existing product portfolio and diplomatic networks for short-term market access and transitioning toward Diversification through co-development of advanced defense technologies with regional partners. This two-phase strategy offers a balance between risk mitigation and long-term competitive advantage.